PEMBUATAN ARANG AKTIF DARI LIMBAH AMPAS TEBU SEBAGAI ADSORBEN ION FE2+ DAN CO2+ - Faucut Sarah (Jurnal Penelitian Pendidikan IPA, 2018)
Producing active charcoal to be absorbent for ion Fe2+ and Co2+ had been done by using waste of bagasse. The objective of study was to utilize waste of bagasse to be active charcoal, so it can be used for absorbent. Initially, it was carbonized by using pyrolysis at temperature of 300-400oC for 5 hours. Then, it was activated by solving to ZnCl 2 10% for 24 hours, filtered and washed by using distilled water. Wet active charcoal was drained in oven for 9 hours at temperature of 110oC. After that, the analysis stage was started by inserted the absorbent into 10 mL samples which are contained various concentration of ion Fe2+ and Co2+ with variation of 1 gram, 2 grams, and 3 grams for 10 ppm solution. The, it was stirred by contacted time of 10, 20, and 30 minutes. By the previous treatment, it was indicated that the best contacted time for Fe2+ is 30 minutes with 3 grams absorbent which is showed by color change from yellow to colorless with a removal percentage of 95%. For the same case, Co2+ has removal percentage of 98% for 3 grams absorbent with contacted time of 30 minutes which is showed by color change from pink to faded. Keywords: waste of bagasse, absorbent, active charcoal, pyrolysis, Co 2+ , Fe 2+